Ventilation variability of Labrador Sea Water and its impact on oxygen and anthropogenic carbon: a review - Rhein, Monika; Steinfeldt, Reiner; Kieke, Dagmar; Stendardo, Ilaria; Yashayaev, Igor (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences, 2017)
Ventilation of Labrador Sea Water (LSW) receives ample attention because of its potential relation to the strength of the Atlantic Meridional Overturning Circulation (AMOC). Here, we provide an overview of the changes of LSW from observations in the Labrador Sea and from the southern boundary of the subpolar gyre at 47° N. A strong winter-time atmospheric cooling over the Labrador Sea led to intense and deep convection, producing a thick and dense LSW layer as, for instance, in the early to mid-1990s. The weaker convection in the following years mostly ventilated less dense LSW vintages and also reduced the supply of oxygen. As a further consequence, the rate of uptake of anthropogenic carbon by LSW decreased between the two time periods 1996–1999 and 2007–2010 in the western subpolar North Atlantic. In the eastern basins, the rate of increase in anthropogenic carbon became greater due to the delayed advection of LSW that was ventilated in previous years. Starting in winter 2013/2014 and prevailing at least into winter 2015/2016, production of denser and more voluminous LSW resumed. Increasing oxygen signals have already been found in the western boundary current at 47° N. On decadal and shorter time scales, anomalous cold atmospheric conditions over the Labrador Sea lead to an intensification of convection. On multi-decadal time scales, the ‘cold blob’ in the subpolar North Atlantic projected by climate models in the next 100 years is linked to a weaker AMOC and weaker convection (and thus deoxygenation) in the Labrador Sea.